ANALISIS PERBANDINGAN KINERJA KEUANGAN PT KOBEXINDO TRACTORS TBK DAN PT UNITED TRACTORS TBK - Prayitno, Teguh; Rismayani, Maya; Vicky Firmansyah, Muhammad; Ramadhan, Yanuar (Penerbit Lafadz Jaya, 2025)
PT Kobexindo Tractors Tbk (KOBX) is a newcomer company engaged in the distribution of heavy equipment, spare parts and after-sales services in Indonesia. Established in 2002, KOBX, which initially focused on selling heavy equipment for mining, diversified its business into the construction segment. The Develon and Shantui brands are its mainstay products, even the Shantui bulldozer is recorded as the bulldozer with the highest sales in China and number 2 internationally. PT United Tractors Tbk (UNTR) as a comparison is a large company in the heavy equipment sector that has started its business since 1973 with the Komatsu brand of heavy equipment. This study aims to determine the development of the heavy equipment business run by KOBX through an analysis of the financial performance of PT Kobexindo Tractors Tbk and comparing it with PT United Tractors Tbk as a comparison. This study uses a quantitative descriptive approach. The data collection technique in this study is the documentation method, namely by accessing the financial reports of the two companies listed on the Indonesia Stock Exchange during the period 2022-2024. From the financial report analysis, it can be seen that the stability & efficiency of KOBX's financial performance is still below UNTR. Trend Analysis KOBX and UNTR have different financial strategies and asset and liability management capabilities. Index analysis shows that KOBX's large funding base causes lower financial stability than UNTR. While Common Size Analysis states that KOBX is more vulnerable to liquidity risks and short-term liabilities than UNTR, which is more solid and financially healthy.